Creating Diasporic Worlds - Stylianou-Lambert, Theopisti (My University, 2026)
Creating Diasporic Worlds, an art commission award by the Cyprus High Commission in the UK, the Hellenic Institute, the Centre for Greek Diaspora Studies, the Centre for the GeoHumanities at Royal Holloway, University of London, and the Fitzwilliam Museum – University of Cambridge
Keywords: Arts and entertainment